Development and Application of the Principle “nemo plus iuris” in the Roman Law and the Contemporary Slovak Law - Ján Ivančík (Societas et Iurisprudentia, 2020)
Is the principle nemo plus iuris ad alium transferre potest, quam ipse haberet valid in the modern legal order? It is one of the most quoted original Roman principles in the case law; however, modern social and economic relationships create new circumventions of the aforementioned principle. The author deals with the development and application of this principle during the age of the Roman Empire and its current application in the Slovak legal order.